2013
DOI: 10.1007/s12032-013-0484-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-130b is an EMT-related microRNA that targets DICER1 for aggression in endometrial cancer

Abstract: Endometrial cancer (EC) is the most common gynecologic malignancy, but the molecular events involved in the development and progression of EC remain unclear. Certain microRNAs (miRNAs) and DICER1 play important roles in cell motility and survival. This study investigated the role of miR-130b and DICER1 in EC. We profiled miR-130b and DICER1 expression in clinical samples explored its relationship with clinical parameters. A luciferase reporter assay assessed the miR-130b targeting potential of DICER1. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 20 publications
2
37
0
Order By: Relevance
“…For example, in colorectal cancer cell lines, miR-130b directly targeted peroxisome proliferator-activated receptor γ (PPARγ), which regulates some key mediators of cell proliferation, such as P21, cyclin A, and PTEN, thus increasing cell proliferation [27]. In another study involving endometrial cancer cell lines, miR-130b suppressed DICER1 expression and led to the deregulation of miR-200, together with some other EMT-related proteins [38]. In the present study, we showed that miR-130b was involved in cell cycle control and the EMT process and, therefore, promoted cell proliferation, as well as the invasion and migration of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in colorectal cancer cell lines, miR-130b directly targeted peroxisome proliferator-activated receptor γ (PPARγ), which regulates some key mediators of cell proliferation, such as P21, cyclin A, and PTEN, thus increasing cell proliferation [27]. In another study involving endometrial cancer cell lines, miR-130b suppressed DICER1 expression and led to the deregulation of miR-200, together with some other EMT-related proteins [38]. In the present study, we showed that miR-130b was involved in cell cycle control and the EMT process and, therefore, promoted cell proliferation, as well as the invasion and migration of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Wound-healing assay was performed as described previously [35]. The migration index was defined as the distance traveled by the cell monolayer relative to the gap made by the pipette tip at 0 h.…”
Section: Wound-healing Assaymentioning
confidence: 99%
“…Its role in HNSCC is yet to be elucidated but it is related to epithelialmesenchymal transition (EMT) in endometrial carcinoma [89]. It has also been identified as regulating the tumour suppressor gene RUNX3 in gastric cancer [90].…”
Section: Studymentioning
confidence: 99%